The modern matchmakers. (Economist, 2012)
The article focuses on online dating websites and their claims of using scientific processes to match people successfully. Information is provided on a study by a team of psychologists led by Eli Finkel published in the journal "Psychological Science in the Public Interest" which found that online dating websites use no provably successful algorithm for matching people.